Qualitative and quantitative assessments of radiographic healing of osteochondritis dissecans of the humeral capitellum - Uno, Tomohiro (JSES Int, 2021)
BACKGROUND: Little is known about the optimal timing of early return to sports after which the osteochondritis dissecans (OCD) lesion can completely heal. The aims of this study were to investigate the clinical outcomes of nonoperative treatment and elucidate the relationship between the radiographic findings and the timing for the return to sports. METHODS: We performed a retrospective review of 32 patients who presented with stable OCD of the capitellum and were treated nonoperatively for a minimum of 3 months. The mean follow-up period was 22.1 months. OCD lesions were assessed qualitatively and quantitatively on anteroposterior radiographs of the elbow at 45° of flexion every 3 months. The width of the OCD lesion (OCDw) and lateral width of the normal capitellum were measured and were associated with return to sports activities. RESULTS: In 21 patients (66%), the progression of ossification was seen at a mean period of 4.1 months. Eighteen (56%) had partial union at a mean period of 4.3 months. Twenty-nine cases (91%) returned to sports activities after a mean of 4.6 months. Nine cases (28%) achieved complete union after a mean period of 15.0 months. Fifteen (47%) required surgery after a mean period of 11.8 months. The mean OCDw (%) was 10.2 ± 3.9 mm (56%) at the initial presentation and 8.0 ± 6.0 mm (41%) at the final follow-up examination, and the decrease in OCDw was 2.2 ± 3.1 mm (15%). The mean decrease in OCDw in patients with progression of ossification during the first 3 months was significantly larger than in patients without progression of ossification (4.9 ± 4.7 mm and -0.7 ± 4.5 mm, respectively; P = .002). In patients who had both an OCDw value of <8.0 mm and a lateral width value of >2.0 mm at the time of the return to sports, the rate of successful nonoperative treatment (86%) and complete union (71%) was significantly higher in comparison with other patients (P = .03 and P = .02). CONCLUSIONS: OCD lesions showed difficult healing in the middle one-third of the capitellum. The progression of ossification during the first 3 months was a significant predictor of successful nonoperative treatment and complete union. Surgery should be considered for lesions without the progression of ossification during the first 3 months. We propose both an OCD lesion width of <8.0 mm and a lateral normal width of >2.0 mm as radiographic landmarks of the timing of the return to sports.